DOI: 10.1007/978-3-540-70590-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Proving Quadratic Derivational Complexities Using Context Dependent Interpretations

Abstract: Abstract. In this paper we study context dependent interpretations, a semantic termination method extending interpretations over the natural numbers, introduced by Hofbauer. We present two subclasses of context dependent interpretations and establish tight upper bounds on the induced derivational complexities. In particular we delineate a class of interpretations that induces quadratic derivational complexity. Furthermore, we present an algorithm for mechanically proving termination of rewrite systems with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…The encoding is an adaptation of the procedure in (Contejean et al 2005) to context-dependent interpretations. It is described in detail in (Schnabl 2007, Moser & Schnabl 2008). Once we have built the constraints, we continue using the same techniques as for searching polynomial interpretations: we encode the constraints in a propositional satisfiability problem, apply the SAT solver, and use a satisfying assignment to construct a context-dependent interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The encoding is an adaptation of the procedure in (Contejean et al 2005) to context-dependent interpretations. It is described in detail in (Schnabl 2007, Moser & Schnabl 2008). Once we have built the constraints, we continue using the same techniques as for searching polynomial interpretations: we encode the constraints in a propositional satisfiability problem, apply the SAT solver, and use a satisfying assignment to construct a context-dependent interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…Theorem 6 ( (Moser & Schnabl 2008)). Let R be a TRS and suppose that there exists a compatible ∆-linear interpretation.…”
Section: Context Dependent Interpretationsmentioning
confidence: 99%
“…Example 3.15. Consider the TRS R nc given by the rules 43 : f(n; ) → h(; gs(n; )) 44 : gs(0; ) → 0 45 : h(; g(; n)) → c(; h(; n), h(; n)) 46 : gs(s(; n); ) → g(; gs(n; )) 47 :…”
Section: The Polynomial Path Ordermentioning
confidence: 99%
“…Polynomial complexity analysis is an active research area in rewriting. Starting from [46] interest in automated polynomial complexity analysis greatly increased over the last years, see for example [30,31,45,48,57]. This is partly due to the incorporation of a dedicated category for complexity into the annual termination competition (TERMCOMP).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that termination techniques can be used to study the runtime complexity of a given TRS. See [11,12,22,36], among others. In this subsection, we show that, as expected, bounding the runtime complexity of a TRS, allows us to recover a sup-interpretation.…”
Section: Runtime Complexity Functions As Sup-interpretationsmentioning
confidence: 99%